2019
DOI: 10.3390/molecules24203705
|View full text |Cite
|
Sign up to set email alerts
|

6-Shogaol Inhibits Advanced Glycation End-Products-Induced IL-6 and ICAM-1 Expression by Regulating Oxidative Responses in Human Gingival Fibroblasts

Abstract: Advanced glycation end-products (AGEs) cause diabetes mellitus (DM) complications and accumulate more highly in periodontal tissues of patients with periodontitis and DM. AGEs aggravate periodontitis with DM by increasing the expression of inflammation-related factors in periodontal tissues. 6-Shogaol, a major compound in ginger, has anti-inflammatory and anti-oxidative activities. However, the influence of shogaol on DM-associated periodontitis is not well known. In this study, the effects of 6-shogaol on AGE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 60 publications
0
24
0
Order By: Relevance
“…Oxidative stress plays a critical role in cisplatin-induced renal injury [ 5 , 7 ]. Previous studies have demonstrated that 6-shogaol exerts an anti-oxidative activity [ 17 , 18 ]. Thus, to explore the mechanisms underlying the protective effect of 6-shogaol on cisplatin-induced AKI, we next evaluated the levels of lipid peroxidation markers 4-hydroxynonenal (4-HNE) and malondialdehyde (MDA) [ 19 ] in the kidneys.…”
Section: Resultsmentioning
confidence: 99%
“…Oxidative stress plays a critical role in cisplatin-induced renal injury [ 5 , 7 ]. Previous studies have demonstrated that 6-shogaol exerts an anti-oxidative activity [ 17 , 18 ]. Thus, to explore the mechanisms underlying the protective effect of 6-shogaol on cisplatin-induced AKI, we next evaluated the levels of lipid peroxidation markers 4-hydroxynonenal (4-HNE) and malondialdehyde (MDA) [ 19 ] in the kidneys.…”
Section: Resultsmentioning
confidence: 99%
“…Formation of CML can be inhibited through antioxidant activity to reduce the formation of AGEs by preventing the oxidation of Amadori products and metal-catalyzed glycoxidation ( Dil et al, 2019 ). Inhibition of AGEs formation through methylglyoxal (MGO) blockage has been demonstrated in studies using shogaol ( Nonaka et al, 2019 ) and putrescine ( Park et al, 2017 ). Previous research showed the ability of shogaol to reduce the formation of CML in a BSA/Fructose solution ( Malakul and Pengnet, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of AGEs formation through methylglyoxal (MGO) blockage has been demonstrated in studies using shogaol [24] and putrescine [25]. Research conducted [26] showed the ability of shogaol to reduce the formation of CML in a BSA/fructose solution.…”
Section: Discussionmentioning
confidence: 99%